How video works. - Weise, Marcus, ....-; Weynand, Diana, ....- (Amsterdam : Elsevier, 2004)
Overview/Introduction; Electronic Photography; Scanning; Synchronizing the Signal; Transmitting the Signal; Color Video Color Monitor Setup; Analog Waveform Monitors; Analog Vectorscopes; The Encoded Signal; Digital Theory; Digital Television Standards; High Definition Video; Digital Scopes; Compression; Magnetic Media; Optical Media; Timecode; Audio For Video; Operations Overview; Test Signals & Media Problems
Keywords: Videotechniek